ChemInform Abstract: Transition Metal‐Catalyzed [2 + 2] Cycloaddition Reactions Between Bicyclic Alkenes and Alkynes. Issue 34 (26th August 2014) - Tam, William; Jack, Kelsey; Goodreid, Jordan; Cockburn, Neil
Abstract Review: 102 refs.